Novel IKBKG gene mutations in incontinentia pigmenti: report of two cases - Chen, Huaqing; Ji, Xiaojuan; Lai, Yun; Xie, Ling; Wan, Chunlei; Li, Longnian (Frontiers in Medicine, 2023)
Incontinentia pigmenti (IP), an X-chromosome dominant genodermatosis caused by mutations in the IKBKG/NEMO gene, is a rare disease affecting the skin, teeth, eyes, and central nervous system. Here, we report two pedigrees of IP and detection of two novel mutations in the IKBKG gene associated with IP via genetic analysis. In addition, different gene mutation types can present with different clinical phenotypes, and the same gene mutation type can show different clinical phenotypes. This study provides clinical cases for further study of the genotype and phenotype of IP and enriches the mutation spectrum of IKBKG gene, which provides a basis for genetic counseling and genetic diagnosis of IP in the future.